Geological settings and controls of fluid migration and associated seafloor seepage features in the north Irish Sea. (January 2021) - Coughlan, Mark; Roy, Srikumar; O'Sullivan, Conor; Clements, Annika; O'Toole, Ronan; Plets, Ruth
Abstract: Shallow gas accumulation in unconsolidated Quaternary sediments, and associated seepage at the seafloor, is widespread in the north Irish Sea. This study integrates high-resolution seafloor bathymetry and sub-surface geophysical data to investigate shallow gas accumulations and possible fluid (gas and/or liquids) migration pathways to the seafloor in the northern part of the Irish Sea. Shallow gas occurs broadly in two geological settings: the Codling Fault Zone and the Western Irish Sea Mud Belt. The gas has been recognised to accumulate in both sandy and muddy Quaternary marine near-surface sediments and is characterised by three characteristic sub-bottom acoustic features: i) enhanced reflections, ii) acoustic turbid zones, and iii) acoustic blanking. The seepage of shallow gas at the seafloor has resulted in the formation of morphological features including methane-derived authigenic carbonates, seabed mounds and pockmarks. In many instances, the evidence for this gas as biogenic or thermogenic in origin is inconclusive. Two distinct types of pockmarks are recorded in the Western Irish Mud Belt: pockmarks with a relatively flat centre, and pockmarks with a central mound. Based on our observation and existing models, we infer that the formation of a carbonate crust at the seabed surface is needed as a precursor for the creation of such mounds within pockmarks. The formation processes are interpreted to be different for sandy versus muddy sediments, due to variability in erodibility and sealing capacities of the substrate. We suggest that the origin of these features is linked to the presence of deeper hydrocarbon source rocks with existing and reactivated faults forming fluid migration pathways to the surface. This in turn could indicate a mixed thermogenic-biogenic origin for seep-related structures in the study area. These features have significant implications for the future development of offshore infrastructure including marine renewable energy as well as for seabed ecology and conservation efforts in the Irish Sea. Highlights: An integrated methodology is used to assess fluid flow in the north Irish Sea. Characterisation of an accumulation of shallow gas in Quaternary sediments, 17 new pockmarks and an area of seabed mounds. New mechanisms proposed for pockmark and seabed mound formation for this location. Cenozoic faulting and re-activation of older faults generates pathways for fluids to migrate to the shallow sub-surface. At the seabed, sediment properties play a strong role in the morphological expression of fluid seepage structures.